PENGARUH KONSENTRASI NATRIUM METABISULFIT DAN LAMA BLANCHING TERHADAP MUTU CABAI MERAH (CAPSICUM ANNUUM L.) KERING - Akhyar Ali; Yusmarini '; Ipa Solihah (Jurnal Sagu, 2002)
The effect of natrium metabisulphide with different concentration and tlic blanchingtime on quality of dried red chili was carried out. Result showed that the difference concen-tration of natrium metabisulphide and the blanching time scpcratcly influence the content ofoleoresin and vitamin C, however they do not affect significantly of water content of driedred chili. Interaction of natrium metabisulphide and the blanching time influence the watercontent, vitamin C, oleoresin and colour of dried red chili. Concentration of 0 3 of natrium %metabisulphide and 5 minute blanching gave the best result.